2017
DOI: 10.1007/s00264-017-3500-8
|View full text |Cite
|
Sign up to set email alerts
|

Two stage revision hip arthroplasty in periprosthetic joint infection. Comparison study: with or without the use of a spacer

Abstract: Purpose The aim of this study was to compare two methods of two-stage surgery for PJI (periprosthetic joint infection) after THA (total hip arthroplasty): one with and one without the use of an antibiotic-loaded cement spacer. Methods This retrospective study was performed on 99 consecutive patients (99 hips) with a minimum follow-up of 24 months. Patients were divided into two groups: (1) in whom the operation was performed using a spacer, and (2) for whom a spacer was not used. Results For the whole cohort, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…Therefore, with similar leg length discrepancy rates and median discrepancies, two-stage revision involving resection arthroplasty with a short interval was comparable with two-stage revision using a PMMA bone cement spacer during the interval. Other authors described more pronounced leg shortening in case of delayed reimplantation [24]. If an early reconstruction after resection arthroplasty is performed, results were similar to those in whom a spacer was used [10].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Therefore, with similar leg length discrepancy rates and median discrepancies, two-stage revision involving resection arthroplasty with a short interval was comparable with two-stage revision using a PMMA bone cement spacer during the interval. Other authors described more pronounced leg shortening in case of delayed reimplantation [24]. If an early reconstruction after resection arthroplasty is performed, results were similar to those in whom a spacer was used [10].…”
Section: Discussionmentioning
confidence: 57%
“…The present study did not include an evaluation of functional outcome. However, in the retrospective study by Marczak et al, the final Harris hip score (HHS) and visual analogue scale (VAS) score showed no difference between patients treated with a two-stage revision with or without spacer, while the final WOMAC (Western Ontario and McMaster Universities osteoarthritis index) score showed a better outcome in the spacer group [24]. The decision to use a spacer in this study was based on the preferences of the surgeon and local bone deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of a temporary antibiotic-impregnated spacer in the interim period is used worldwide in two-stage exchange arthroplasty, since it enables preservation of the joint space, ensures high local concentrations of antibiotics, and the reimplantation sometimes can be easier due to the absence of scar tissue in the acetabulum and medullary canal [43]. Nevertheless, spacers may act as a foreign body to which microorganisms may adhere, grow, and maintain infection [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“… 9 Marczak et al reported a significant difference in terms of functional improvement (according to the Harris hip score) between their spacer and a non-spacer cohort treated with two-stage replacement due to PJI. 24 The same authors reported an infection recurrence rate of 9.2% that was comparable in the two groups.…”
Section: Discussionmentioning
confidence: 83%